PENGETAHUAN PEMBUKUAN SEDERHANA PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) TERHADAP LAPORAN KEUANGAN: (Studi Di Desa Larike, Maluku Tengah) - Dynne Andriany; Muhammad Iqbal Husein (Politeknik Negeri Ambon, 2023)
The purpose of this study was to determine the extent to which the knowledge of simple bookkeeping by MSME business actors on financial reports in the village of Larike. This type of research is a qualitative research. The informant in this study were mothers of MSME actors in Larike village as many as 10 people, each of whom had their own business. In this study, data collection was carried out, namely Focus Group Discussion or FGD. The data analysis technique used by the researcher was by using qualitative data analysis techniques. The results of this study indicate that the simple bookkeeping that MSME actors make is only in the form of notes about purchases and sales, as well as financial reports they only make in a simple way to the extent of what they understand to see the profit or loss they get at one time. the production process without separating into reports such as balance sheets, profit/loss and reports on changes in capital. This is due to the lack of knowledge they have about good and correct bookkeeping and preparation of financial statements